To write an equation in point-slope form using the two points \( A(-4, 4) \) and \( B(-2, 0) \), we first need to find the slope of the line that passes through these points.
Step 1: Calculate the slope (m)
The slope \( m \) is calculated using the formula:
\[
m = \frac{y_2 - y_1}{x_2 - x_1}
\]
Using the points \( A(-4, 4) \) (where \( x_1 = -4, y_1 = 4 \)) and \( B(-2, 0) \) (where \( x_2 = -2, y_2 = 0 \)):
\[
m = \frac{0 - 4}{-2 - (-4)} = \frac{-4}{-2 + 4} = \frac{-4}{2} = -2
\]
Step 2: Use point-slope form
The point-slope form of a line is given by:
\[
y - y_1 = m(x - x_1)
\]
We can use either point \( A(-4, 4) \) or point \( B(-2, 0) \). Let's use point \( A \):
- \( m = -2 \)
- \( (x_1, y_1) = (-4, 4) \)
Substituting into the point-slope form:
\[
y - 4 = -2(x - (-4))
\]
This simplifies to:
\[
y - 4 = -2(x + 4)
\]
Alternatively, using point \( B(-2, 0) \):
- \( (x_1, y_1) = (-2, 0) \)
Substituting gives:
\[
y - 0 = -2(x - (-2))
\]
Which simplifies to:
\[
y = -2(x + 2)
\]
Final Equation
Thus, the equation in point-slope form for the line passing through points \( A \) and \( B \) can be written as:
-
Using point \( A \):
\[
y - 4 = -2(x + 4)
\]
-
Using point \( B \):
\[
y = -2(x + 2)
\]
Both forms are valid and represent the same line.